Análise da habilidade de atenção conjunta em interações educadora-bebê: um estudo em contexto de creches - Albuquerque, Jéssica Andrade de (2021)
This thesis highlights the educator-infant interactions in the context of daycare centers and highlights the relevance of the socio-cognitive ability of joint attention as an important element for the overall development of children, being organized in three studies that explore the theme. The first study consists of a systematic review of the repercussions of joint attention on children's social cognition in educator-infant interactions in daycare settings. The review followed the recommendations of the Preferred Reporting Items for Systematic reviews and Meta-Analyze (PRISMA) and the analysis of the selected studies revealed that infants engaged in episodes of joint attention with their educators showed the development of communication and oral language, started to be more interested in the partner's actions, to communicate their intentions more frequently and to actively direct attention to the object or activity of interest, which made it possible to affirm that the joint attention established between educator and infant, in daycare settings, reverberates in the infant's social cognition. The second study refers to a survey carried out in five public day care centers, and aimed to understand the conceptions of five child educators about their work with babies, discussing the repercussions of the established interactions. The results of this study showed a dissonance between the verbalizations of kindergarten educators about the development of infants, their performance in daycare centers, and what theoreticians of developmental psychology of historical-cultural basis postulate and the official documents that guide Brazilian early childhood education on the subject. The impact of these conceptions for the established interactions and the relevance of continuing in-service training aimed at early childhood educators are discussed, to promote practices based on scientific theoretical-methodological assumptions that emphasize the early childhood education space as a promoter of learning and development. The third study addresses a longitudinal research that investigated the configurations of joint attention in educator-infant interactions in day care centers at 7, 9 and 12 months of life for babies, in a situation of free and structured play. The results of this study demonstrated different configurations of the skill of joint attention over the three periods of development observed and the emergence of other socio-communicative and linguistic skills that mobilize and redirect interactions with educators in each period. It is considered that the set of results extracted from the present thesis contributes to the discussion about the development processes of infants in daycare centers in the first year of life, for the planning of interventions in the scope of early childhood education, to promote actions that enhance development in daycare centers and in proposing future research in the area.